The Effectiveness of Outdoor Learning-Based IPA Learning on Concept Mastery and Science Process Skills of Students in Class VIII SMP Negeri Sumber Rejo - Sulistiyono, Sulistiyono; Triyanti, Merti (Universitas Ahmad Dahlan, 2023)
This study aims to improve students' mastery of concepts and skills by using outdoor learning-based science learning, the method used in this study is a quasi-experiment (pseudo- design) with a randomized control group pretest-posttest design. The population of this study was the 8th grade students of SMP Negeri Sumber Rejo, then the research sample was selected through simple random sampling method. The research subjects used were students of class VIIIA as the experimental class and students of class VIIIC as the control class. Research data were obtained through test instruments and non-test instruments. Data analysis techniques used percentages for science process skills and t-tests for concept understanding. Hypothesis testing with t-test using SPSS program obtained Sig value 0.000 <0.05, then Ha is accepted and Ho is rejected, which means that outdoor learning-based science learning is effective to improve students' concept understanding and science process skills. Based on the observation of students' science process skills at the first meeting in the experimental class was 79.7% while in the control class was 64.6%. The average value of the observation of science process skills at the second meeting in the experimental class was 84.8% while in the control class was 74.6%.